HUMAN RIGHTS CHILDREN AND WOMEN PROTECTION IN THE VERSES OF AL-AHKAM - Fauzi Fauzi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This article intends to explain the position of human rights in relation to the protection of children and women in the Qur’ān. Based on the fact that the rights to children and women are exploited across history, the author intend to examine normative legal values extracted from the Holy Qur’ān as a way of life in order to encourage each individual to respect their rights. This research was conducted with a study of documentation as the technical analysis of data collection and analyzed by semi-thematic of ayat al-Ahkam. From a number of verses traced it can be concluded that human rights are a concern for their substance to provide more comprehensive protection to children and women. The protection of children includes: protection of survival, getting adequate nutrition from birth to the appropriate time limit, getting fulfillment of the needs and rights of development of reason through education. Meanwhile protection for women in the form of; protection through marriage and stipulation of ‘iddah when a husband’s divorce and death occur, the right to hear complaints and difficulties is experienced and get equal rights in various joints of life as servants of God